Plant-based bioactive compounds for grain storage: a comprehensive review - Zemenu Tadesse Adimas; Mekuannt Alefe Adimas; Biresaw Demelash Abera (Cogent Food & Agriculture, 2024)
The post-harvest loss of grain is a global concern, especially for developing countries where food security is a big challenge. Botanical plants are called green pesticides, which can affect various insect pests in different ways. Essential oils have a broad range of bioactivity when it comes to combating agricultural pests. Moreover, spices are potential alternatives to preserve grains from insect infestations due to their different characteristics (repellent, deterrent, and insecticidal). The aim of this review is to provide an overview of plant-based products, including their mode of action, bioactive components, and targeted pests and insects for grain storage.